Evolution and Impact of Switchbacks Throughout the Heliosphere - Mallet,A; Shi,C; Tenerani,A; Agapitov,O; Akhavan-Tafti,M; Badman,S; Bizien,N; Bowen,T; Desai,MI; Drake,JF; Horbury,T; Larosa,A; et al. (Space Science Reviews, 2026)
Magnetic switchbacks are large-amplitude fluctuations in the interplanetary magnetic field, and appear frequently in the near-Sun solar wind explored recently by Parker Solar Probe: these new observations have prompted many new studies into their properties and origins. Here, we first review what is known about how switchbacks evolve as they travel away from the Sun: both in terms of their expansion-driven growth and their decay due to various processes like turbulence, reconnection, dispersion, parametric instability, and interaction with interplanetary shocks. We then review the current state of knowledge on how switchbacks impact the physics of the solar wind as a whole: in terms of the turbulent cascade, acceleration and heating of the wind, modification of the open solar flux and scattering of energetic particles. Finally, we suggest future studies to further our understanding of switchback evolution and impacts on the heliosphere.